Social Costs of Setback Distances for Onshore Wind Turbines: A Model Analysis Applied to the German State of Saxony - Felix Reutter; Martin Drechsler; Erik Gawel; Paul Lehmann (Environmental and Resource Economics, 2023)
Wind power is a key for decarbonizing economies. Yet, wind turbines can produce negative environmental externalities. These include bird collisions and disamenities for residents. Setback distances for onshore wind turbines to settlements and bird nests are a common policy instrument to address these externalities. In this paper, we evaluate the cost-effectiveness of setback distances. We use a spatially-explicit model to investigate the social costs of different options for setbacks to settlements and red kite nests. In terms of social costs, we consider production costs and external costs associated with residents' disamenities and red kite impacts given an exogenously set wind energy production target. The model is applied using data for the German State of Saxony. Three key results are: (1) More restrictive setbacks may increase social costs. (2) Uniform red kite setbacks reduce social costs rather than uniform settlement setbacks. (3) Differentiated settlement setbacks for different settlement types lead to substantially lower social costs than uniform setbacks.
Keywords: 330; Wind turbines; Externalities; Setback distances; Social costs; Spatially-explicit modeling